Analyzing the Influence of Bank Competition on Credit Risk: Perspectives from Indonesia's Dual Banking System - Adella Febriana; Suhel; Sri Andaiyani (Jurnal Ekonomi Kuantitatif Terapan, 2024)
This study analyzes the effect of competition banks on credit risk in the dual banking system in Indonesia. Thisresearch was conducted using a purposive sampling technique in selecting a sample of 5 conventional commercial banksand 5 Islamic commercial banks. The method used is the Generalized Method of Moments (GMM) from 2011 to2020. Credit risk for Conventional Banks is measured by the value of Non-Performing Loan (NPL), while IslamicBank Financing is measured by the value of Non-Performing Financing (NPF). The results of this study indicatethat Return on Assets (ROA) for Conventional Banks and Islamic Banks has a significant effect on credit risk inthe dual banking system, Loan to Deposit Ratio (LDR) for Conventional Banks does not have a significant effect onNon-Performing Loan (NPL) while Financing to Deposit Ratio (FDR) of Islamic Banks has a significant level 2influence on Non-Performing Financing (NPF). Bank size does not have a significant influence on credit risk in thedual banking system, and the Lerner Index for Conventional Banks has a significant effect on Non-Performing Loan(NPL), while the Lerner Index for Islamic Banks has no effect on Non-Performing Financing (NPF). The CentralBank in making policies can see that the level of competition for banks in the dual banking system in Indonesia iscategorized as a monopolistic competition market, where each bank has its own market segment so that it has marketpower that is strong enough to set prices that are relatively